Delusional Infestation in a Patient with Renal Failure, Metabolic Syndrome, and Chronic Cerebrovascular Disease Treated with Aripiprazole: A Case Report - Bernardo Carpiniello; Federica Pinna; Raffaella Tuveri (Case Reports in Medicine)
Delusional infestation is an aspecific psychiatric condition manifested either as a primary psychotic disorder or a secondary disorder induced by a wide range of very different medical conditions. Both primary and secondary delusional infestations seem to respond to typical and atypical antipsychotics. The latter are considered the first-line treatment although the use of second-generation antipsychotics featuring a higher metabolic, cardiovascular, and renal tolerability is preferable in secondary cases, which often occur in patients with multiple, severe medical conditions. We report a case of a 72-year-old patient affected by delusional infestation associated with severe renal failure, metabolic syndrome, hypertensive cardiopathy, and chronic cerebrovascular disease.